perencanan sistem pengelolaan sampah dengan pemanfaatan sistem informasi geografis - Puja Rizki Bahari; Yudi Antomi; Indang Dewata; Nurhasan Syah (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to increase the reach of waste management system services in Pariaman City by utilizing geographic information systems. This research is descriptive. The data collection technique used observation. The sampling technique used was total sampling. The data analysis technique used Interpretative Structural Modeling and Geographic Information Systems. The planning results include the proposal of 9 new temporary waste storage locations and the optimization of waste transportation services. This proposed system significantly increases the coverage of waste management services in Pariaman City: from 51.41% (640.66 hectares) of the total residential area of 1,245.47 hectares, to 81.67% (1,017 hectares) served